Pengaruh Kecepatan Pengadukan dan Waktu Kontak Ampas Kulit Durian (Durio Zibethinus L.) terhadap Penyerapan Ion Logam Tembaga (II) dengan Metode Batch - Bastian, Vadianda; Nasra, Edi (Lembaga Yasin AlSys, 2024)
One of the effective methods in handling the impact of pollution by copper ion is the biosorption method using durian peel powder (Durio Zibethinus L.). The purpose of this research is to determine the optimum absorption conditions and the optimum capacity for absorption of copper metal ions (Cu2+) using the batch method with variations in pH, concentration, stirring speed, contact time, and mass of biosorbent. The results of the research showed that the optimum conditions for the absorption of Cu2+ metal ions were at pH 6, concentration of 220 ppm, stirring speed of 250 rpm, contact time of 90 minutes and mass of biosorbent 0,4 gram was 7,788 mg/g. The adsorption isotherm of Cu2+ metal with durian skin biosorbent (Durio Zibethinus L.) tends to follow the Langmuir isotherm equation with a determinant coefficient (R) of 0,1854. Durian peel powder was characterized by the FTIR instrument, before being activated, after being activated, and after contacting the analyte there were functional groups, namely hydroxyl (O-H), alkene (C=C), carbonyl (C-O), and ether (-COC) groups.